Dependence modeling with copulas - Embrechts, Paul; Neslehova, Johanna (Henry Stewart Talks, 2007)
Impact of extremes and dependence in finance and insurance, Correlation issues, Copulas and Sklar's theorem, Copula generation, Frechet-Hoeffding bounds, Limitations of correlation, Rank correlation measures, An application to credit risk, Tail dependence, Bounds on risk measures, Critical appraisal
Archived at 2022/04/04